2017
DOI: 10.1111/bph.13855
|View full text |Cite
|
Sign up to set email alerts
|

Natural alkaloid bouchardatine ameliorates metabolic disorders in high‐fat diet‐fed mice by stimulating the sirtuin 1/liver kinase B‐1/AMPK axis

Abstract: Bou may have therapeutic potential for obesity-related metabolic diseases by increasing the capacity of energy expenditure in adipose tissues and liver through a mechanism involving the SIRT1-LKB1-AMPK axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Our data suggest the possibility that NecB can be selected as a therapeutic candidate for preventing aging-related diseases. Since the SIRT1, AMPK, and mTOR pathways have been implicated in aging and age-related diseases [13,18,32], we focused on these three pathways to elucidate the molecular mechanism of NecB effect on old HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest the possibility that NecB can be selected as a therapeutic candidate for preventing aging-related diseases. Since the SIRT1, AMPK, and mTOR pathways have been implicated in aging and age-related diseases [13,18,32], we focused on these three pathways to elucidate the molecular mechanism of NecB effect on old HDFs.…”
Section: Discussionmentioning
confidence: 99%
“…This was essentially based on the protocols used in our recent studies (Rao et al, ). Liver samples or cells were lysed in ice‐cold RIPA extract buffer (Beyotime, Cat# P0013C, Chengdu, China) supplemented with a mixture of protease inhibitors (Roche, Cat# 4693006001, Guangzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…This was essentially based on the protocols used in our recent studies (Rao et al, 2017). Liver samples or cells were lysed in ice-cold RIPA…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that SIRT1 plays a critical role in lipid metabolism by modulating the activity of transcription factors [14]. In mice and obese patients fed with a high-fat diet, the activity and expression of SIRT1 were significantly decreased, which attenuated the mobilization of fatty acids and promoted the occurrence of metabolic disorders [15][16][17]. In addition, mounting evidence indicates that a long-term, high-calorie-diet induced liver steatosis is promoted by increasing the expression of SIRT1 in animals [18,19].…”
Section: Introductionmentioning
confidence: 99%